MATH

posted by .

y = 2/x^-8

rewrite

differentiate

simplify

• MATH -

I assume that for rewriting it would be

rewrite -2(8x^7)
differentiate 2(-8x^-8-1) so -16x^-9
n i don't know how i simplify it

Similar Questions

1. trigo help!

1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
2. calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
3. MATH

9√x/x a) rewrite b)differentiate c)simplify
4. math-check

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
5. math

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
6. Math

1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 + 4e^x)^5 answer: 20e^x (3+ 4ex)^4 c. y= (e^x - 1) / x^2 answer: (xe^x - 2e^x …
7. Math

1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 + 4e^x)^5 answer: 20e^x (3+ 4ex)^4 c. y= (e^x - 1) / x^2 answer: (xe^x - 2e^x …
8. Math

I have solved the following and I am writing just their answers with it, please let me know if these are correct. thanks 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify y= (e^x - …
9. math

Differentiate, do not simplify. a) y=(3x+2)(x^2-7) b) x^3+3y^2=36
10. Calculus-Math

Complete the table without using the Quotient Rule. Function y=2x^(7/2)/x Rewrite y= Differentiate y'= Simplify y' =

More Similar Questions